Purification of natural gas using thermally rearranged polybenzoxazole and polyimide membranes – a review: part 2. Issue 10 (October 2016) - Woock, Tucker; Bjorgaard, Stacy; Tande, Brian; Alshami, Ali
Abstract : This feature article – published in two parts – focuses on the evolution of polyimide as a gas separation membrane, its subsequent transformation into polybenzoxazole and various studies done to optimise the separation ability of polybenzoxazole. The first instalment, which appears in the September 2016 issue of Membrane Technology, provides theory and background, including details of the solution-diffusion model and a description of fractional free volume. It also discusses the limitations of membrane separation and the permeability/selectivity trade-off, and covers physical ageing, plasticisation, polyimide synthesis, design of polyimide, thermal annealing and cross-linking. Discussing thermally rearranged polybenzoxazole in detail, the second instalment – which appears here – looks at the design of polybenzoxazole, the industrial viability of membranes made from this material, a summary of its performance and future outlook and conclusions.